Qualification of the ARA TWT for laminar flow testing. (November 2014) - Allen, N.; Lawson, S.; Maina, M.; Alderman, J.
Abstract: The current drive towards reducing the environmental impact of aircraft necessitates the ability to evaluate techniques for promoting natural laminar flow in a large scale wind tunnel facility. A test was undertaken on the M2355 variable sweep model to obtain temperature sensitive paint (TSP) and hot-film data from which the transition locations at a range of sweep angles and flow conditions could be identified. The TSP technique has been shown to be a reliable method for determining transition on suitably treated wind tunnel models. Pressure data were also acquired and interpolated to provide the input to the laminar boundary layer code, BL2D, the output from which was used in the linear stability analysis code, CoDS, to calculate the N -factor for the ARA TWT (Transonic Wind Tunnel) facility. Two sets of N -factors were calculated, firstly using incompressible analysis with stationary crossflow and secondly using compressible analysis with travelling crossflow. In both analyses the Tollmien-Schlichting and crossflow cases were calculated together, rather than separating the cases before running the analysis. The resulting N -factors indicate a degree of scatter typical for experimental data. The N -factor based on incompressible theory for crossflow was found to be approximately 7 and for Tollmien-Schlichting (T-S), approximately 11. The results of the wind tunnel test and the analysis carried out are considered to be the first steps towards establishing a methodology for performance testing, in atmospheric tunnels such as the TWT, for aircraft designed to have significant regions of laminar flow. The project has also provided a body of experimental test data which will be valuable for future research into development and validation of laminar flow methods.